PHARMACOTHERAPEUTIC ACTION ANALYSYS OF MINERAL SUBSTANCES OF MEDICINAL PLANTS, WHICH ARE USED IN THYROID GLAND DISEASES - Vladymyrova Inna; Georgiyants Victoriya; Savelieva Elena (Scientific Journal of Pedagogy and Economics, 2019)
Diseases of thyroid gland refer to the most widely spread ones, and are accompanied by the change of hormonal background of the human organism in the whole and lead to disorders of vitally important processes in other organs, triggering appearance of concomitant diseases. Among major causes of thyroid gland diseases are psychological and emotional overloads; malnutrition and unbalanced nutrition that results in deficiency of mineral substances and vitamins in the organism; radioactive conditions and unfavorable ecological situations; chronic diseases. Taking into account such a great role of macro- and microelements in the normal work of the thyroid gland, it is necessary to provide their physiologically necessary content in the organism. The sources of mineral substances can be medicinal plants and remedies made of them. Therefore, the aim of the work was to determine content of macro- and microelement composition of medicinal plants - Lycopus herb, Feijoa leaves, Cetraria islandica thalli, Bugleweed European herb, Genista herb, leaves of Lemna minor, thalli of Fucus vesiculoses and thalli of Laminaria, which are used in treatment of thyroid gland diseases and their water extracts and 10 %, 30 % and 50 % alcohol tinctures. Quantitative content determination of macro- and microelements has been carried out by the atomic emission spectrography method. Quantitative determination of general iodine content has been performed by the iodometry method (titrant – 0.01 М sodium thiosulphate solution) after preliminary burning of the raw material in the alkaline solution by the methodology of State Pharmacopoeia of Ukraine 2.0 volume 3, monograph «Buri vodorosli». The presence of 15 macro and microelements has been determined in the result of the performed spectral analysis of the studied types of medicinal plant raw materials and their extracts. Silicium, mangan, magnesium, calcium, sodium and potassium are contained in comparatively big amounts. When determining qualitative and quantitative content of mineral substances our attention was focused on the elements which had great significance at diseases of thyroid gland, the deficiency or misbalance, which can damage the thyroid gland or other organs functioning, the use of which can eliminate negative symptomatic manifestations in diseases of thyroid gland (Fe, Mn, Mg, Ca, Cu, Zn, Se, I). The representatives of brown algae – Laminaria (0,11 %) and Fucus (0,05 %) and also the representative of fresh water reservoirs – duckweed (0,028 %) are characterized by the highest iodine content. The samples of Laminaria, Fucus, Feijoa and Lemna (duckweed) were characterized by the highest iodine content. The most maximum iodine content had water extracts, when ethyl alcohol concentration was increased, the iodine content didn’t change significantly. High selenium content has been determined in the thalli of Laminaria (0,81 mg/kg), Lemna (duckweed) (0,72 mg/kg) and fresh Feijoa fruit (0,31 mg/kg). The highest selenium content (mkg/l) had water Fucus extract (40) and 50 % Lemna (duckweed) tincture (14). There is an interesting fact, that iodin: selenium ratio in these samples was 1:4(5), that can stipulate similar mechanisms of the effect for thyroid gland. Among the tested substances high selenium and iodine content had simultaneously Laminaria samples – 5 % tincture (3,8) and 10 % tincture (6,6). Though the iodine: selenium ratio had another character and made 18(19):1.